EFFECT OF Telenomus remus NIXON (HYMENOPTERA: SCELIONIDAE) DENSITY ON CONTROL OF Spodoptera frugiperda (SMITH) (LEPIDOPTERA: NOCTUIDAE) EGG MASSES UPON RELEASE IN A MAIZE FIELD - FIGUEIREDO, MARIA DE LOURDES CORRÊA; DELLA LUCIA, TEREZINHA MARIA CASTRO; CRUZ, IVAN (REVISTA BRASILEIRA DE MILHO E SORGO, 2010)
The impact of releasing different densities (0, 6, 9 and 12 adult females m-2) of the egg parasitoid Telenomus remus Nixon on maize plants artificially infested with Spodoptera frugiperda (Smith) egg masses (one m-2) was evaluated. Egg masses were pinned in the midrib of the plant 36 days after planting. One egg mass contained approximately 65 eggs. The experimental design was in a randomized complete block design with five replications (16 m2 plots). There was a significant effect on percentage of parasitism egg masses. The highest parasitism values were verified in plots where 9 or 12 females of T. remus m-2 were released, respectively, 74 and 88.3 %. The relationship between percentage of parasitized egg masses and parasitoid densities was quadratic (Y = 16.8 + 9.98 X – 0.35 X2, r2 = 0.99). The natural occurrence of Trichogramma spp. was relatively constant over the egg masses fixed on maize plants (52.5%). However, the average T. remus parasitism on the eggs of a mass was much higher, representing 80.4% while the parasitism was only 21.3% in the case of Trichogramma. The presence of both parasitoids was responsible for up to 97.5% of parasitism, obtained from plots with a released density of 12 T. remus female m-2.